Applying Georadar method to research on specimens and models in Vietnam - Nguyen, Văn Giảng; Nguyen, Huy Vững; Jarzyna, Jadwiga; Zietek, Jerzy; Nguyen, Văn Dương (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
On the basis of the continuous development of electronic technology and information technology, in recent years, geophysical measuring devices near–surface have been improved in both hardware and software. We have used a combination of some modern geophysical devices such as Pulse Ekko 100A, RAMAC GPR, Terrameter SAS 4000, Supersting R1/IP, CG-5 Autograph to build some models and identify some information the number of objects near–surface to serve the explanation of the geophysical data sequence collected during the survey of geological structures by the geophysical equipment system. Standard models such as soil, sand and common rocks in the geological structure component near–surface distributed in the regions of Vietnam are collected and identified by us parameters. Basic physics at the laboratory analysis of national standard samples according to international standards in Vietnam and Poland. Physical parameters such as resistance, electrical conductivity, electricity, magneticity, electromagnetic transmission velocity, attenuation, density, porosity, elastic wave velocity have been measured with the highest accuracy. In addition, we have used a number of modern geophysical measuring devices to build a number of structural models near-surface that exists a foreign object or many common objects in the geophysical survey. These are the first results obtained in the territory of Vietnam with high accuracy to help the research people solve the geophysical data chain to use to quickly reach the actual model suitable to the conditions of Vietnam.